Analysis of miRNA-mRNA Crosstalk in Radiation-Induced Mouse Thymic Lymphomas to Identify miR-486 as a Critical Regulator by Targeting IGF2BP3 mRNA - Zhao, Hainan; Dong, Suhe; Du, Jicong; Xia, Penglin; Liu, Ruling; Liu, Tingting; Yang, Yajie; Cheng, Ying; Cai, Jianming; Liu, Cong; Gao, Fu; Liu, Hu (Frontiers in Oncology, 2021)
Ionizing radiation is one of the common environmental carcinogens. miRNAs play critical roles in the processes of tumor occurrence, development, metastasis and miRNA generation. However, the relationship between radiation-induced carcinogenesis and miRNA is rarely reported. This study is aimed to investigate the effect of miRNAs on radiation-induced carcinogenesis. By using miRNA array and prediction for miRNAs target genes, a miRNA-mRNA crosstalk network was established. With this network, a critical miRNA that was involved in the radiation-induced carcinogenesis could be identified. Subsequently the function of this critical miRNA was confirmed by using knockout mice and cellular experiments. As a result, by the miRNA-mRNA crosstalk network, miR-486 was identified as one of the most down-regulated miRNAs in radiation-induced thymic lymphoma tissues compared to normal tissues. miR-486 is involved in the development of radiation-induced thymic lymphoma and inhibited proliferation of mouse lymphoma cells by targeting IGF2BP3 mRNA. The adenovirus over-expression miR-486 vector reduced tumorigenesis in vivo. MiR-486 knockout mice have a strong tendency of radiation-induced carcinogenesis. In conclusion, miR-486 inhibits the proliferation of lymphoma cells and tumorigenesis induced by radiation through targeting IGF2BP3